(untitled) (Jurnal Teknologi (Sciences & Engineering), 2025)
Stirrups are included at the intersections of beams, with secondary beams supported by the main beams or positioned where concentrated forces are significant. Additional stirrups must be arranged to enhance the load-bearing capacity at these beam intersections. At these beam intersections, it is necessary to arrange additional stirrups to support the reaction force generated by the secondary beams. At the intersections of the main beams, it is necessary to arrange additional stirrups on the section b+2h (where b and h represent the width and height of the main beam). The use of the stirrup arrangement at the beam intersection, as outlined in the TCVN 5574:2018 standard, has been subject to limited experimental studies. These studies aim to assess whether the stirrup placement at the beam intersection is both reasonable and optimal for ensuring adequate load-bearing capacity in this area. Furthermore, it is essential to investigate the impact of incorporating cocopeat as a partial substitute for sand aggregate in the concrete concerning the performance of these intersecting beams. The research results examined the formation and propagation of cracks, established the relationships between load-vertical displacement and load-compressive (tensile) deformation, explored the impact of additional stirrup arrangements on the behavior of seven experimental reinforced concrete beams, and utilized cocopeat as a sand substitute in concrete with beam dimensions of 0.15×0.2×1.2 m.